Growth of Allopeas gracile under starvation: does it comply with von Bertalanffy growth equation? - Chakraborty, Sabarni; Sikary, Abhijit; Ghosh, Tanisha; Chakraborty, Ashmita; Mandal, Suparna; Nandy, Gargi; Aditya, Gautam (Ecological Questions, 2024)
The growth of the land snails is a primary indicator of the fitness at the individual and population levels. Considering starvation as a limiting factor of growth, the adaptation of the land snail Allopeas gracile (Hutton 1834) (Gastropoda: Subulinidae) was assessed using von Bertanlaffy growth equation. As a starvation treatment, the laboratory reared 0-day old snails were fed at a gap of 1 to 6 days (six levels of starvation treatment) or fed regularly (control). In all instances, the shell length and the biomass (indicators of growth) increased with the time interval complying with the von Bertalanffy growth equation, but the magnitude of maximum shell length, Lmaximum, and the asymptotic length, L∞, decreased, while the growth rate coefficient (k) increased, as the duration of starvation period extended. The k and L∞ were represented as functions of the starvation gap (T) and substituted in classical von Bertalanffy equation, representing a better fit model explaining the growth. The results indicate that the food availability is a crucial factor determining the pace of growth in the land snail A. gracile. As an extension, the present model can be used for the portrayal of the growth of the macroinvertebrates under varying level of starvation.